FATIGUE ANALYSIS OF FREE STANDING DRILLING RISER DUE TO VORTEX INDUCED VIBRATION UNDER EXTREME WEATHER CONDITIONS - RIDZUAN, ANAS FADHIL (IRC, 2018)
A Free-Standing Drilling Riser (FSDR) is a modification to drilling risers that enables rapid disconnection during extreme weather event. This mechanism considered a great solution, as pulling back the whole riser string is a time exhaustive procedure. Vortex induced vibration (VIV) is a well-known important source of fatigue damage of offshore oil exploration and production risers. Extreme weather condition could amplify the effect of VIV towards the FSDR due to higher velocity of current and larger wave impact. Despite various studies has been carried out regarding FSDR, the impact of VIV towards fatigue life of FSDR remains unknown. In this paper, a fatigue analysis of FSDR due to VIV are presented. The objectives of this paper are to determine the location on the FSDR with worst damage rate due to VIV and to estimate the fatigue life of the FSDR under extreme weather condition. Shear7 software, a frequency domain VIV prediction program is used to carry out VIV analysis and fatigue analysis. The result shows that there are two potentially excitation modes of vibration making the FSDR oscillate during extreme weather, thus increasing the damage rate per year and reducing the fatigue life of the riser itself. The worst damage rate is computed at the lower section of the riser, which is at 87.4% of the riser length from the top with lowest fatigue life of 2.23 years.